Resistive switching behavior of Cr-doped SrZrO3 perovskite thin films for random access memory applications - Yang, MK; Kim, DY; Park, JW; Lee, JK (KOREAN PHYSICAL SOC, 2005)
Au/Cr-doped SrZrO3/SrRuO3 thin film structure was fabricated on SrTiO3 (100) substrates by using pulsed laser deposition (PLD). The Cr doped SrZrO3 thin films and SrRuO3 bottom electrodes were epitaxially grown along the (hh0/001) direction. We have studied their resistive switching behavior and memory effects for ReRAM applications. Reproducible insulator-conductor switching behavior was observed with an on/off resistance ratio of about 20. We could also observe that the I-V characteristic of the structure was not linear but diode-like. This agrees well with previous studies on Pr0.7Ca0.3MnO3, and implies that the Au/SrZrO3 : Cr interfaces play an important role in the resistive switching.